БОЖЕСТВЕННЫЕ РЕЛИГИИ И РЕЛИГИОЗНЫЕ ЗАКОНЫ С ТОЧКИ ЗРЕНИЯ КОРАНА - Велигах, М. (Journal of Oriental Studies, 2016)
Құранның басқа да әлемдік діндер мен шариғатқа қатынасын діни тұрғыдан Ислам ойшылдары әр түрлі түсіндіреді. Ең бір назар аударарлық, қызығушылық ту- дырарлық мәселе діни заңдарды жою, өзгерту. Мақа- лада Құран тұрғысынан келгендегі құдайлық дін және діни заңдар туралы жазылған. The discussion of the status of divine religions and its religions is plausible, especially, from the Quran’s and Moslem’s points of view. The question is whether Islam in a general view of religions and or the view of religions and or the view of religions of divine religions has been nullified? Basically, nullification in religions is significant. Religious jurisprudence and words are two parts of religions and the question is how are they together and also without each other. There is an attempt in this article to answer these questions.